What’s Covid19 Got to Do with My Communicative Competence? Self-reflections of Pre-service English Language Teachers in Turkey - Geçkin, Vasfiye (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
With the emergence of the COVID-19 pandemic, nearly all theoretical and practical classes and methods of assessment had to be delivered on digital platforms. This paper reports the use of task-based assessment of the communicative competence of first-year pre-service English language teachers. The aim was to explore the role of the platform where the tasks were held on the students’ self-assessment of their spoken performances. The participants (n=50) evaluated their linguistic, discourse, strategic and sociolinguistics competence on two public speaking tasks. The face-to-face speaking task required elaborating on two famous quotes, whereas the online speaking task had to do with the semiotic analysis of a TV commercial which was decided upon by the teacher candidate. Student evaluations of their communicative competence ranged on a scale from one to five, where one meant very poor and five meant very good. The results indicated that the only component of communicative competence that was viewed to be good was discourse competence in the face-to-face task; however, all the elements of communicative competence were considered to be good except for the sociolinguistic competence in the face-to-screen task. The main findings were (i) that the students had a more positive evaluation of their communicative competence when making online presentations and (ii) that they mostly attributed the differences in their self-evaluations either to the platform or to a combination of the platform and the nature of the task. Yet, face-to-face interaction seems to act as a requirement to improve the sociolinguistic competence of foreign language teacher candidates.